Brief Developmental Exposure to Fluoxetine Causes Life-Long Alteration of the Brain Transcriptome in Zebrafish - Nozari, Amin; Gagné, Remi; Lu, Chunyu; Yauk, Carole; Trudeau, Vance L. (Frontiers in Endocrinology, 2022)
Fluoxetine (FLX) and other selective serotonin reuptake inhibitors are widely used to treat depressive disorders during pregnancy. Early-life exposure to FLX is known to disrupt the normal function of the stress axis in humans, rodents, and teleosts. We used a zebrafish line with a cortisol-inducible fluorescent transgene to study the effects of developmental daily exposure to FLX (54 µg/L) on the transcriptomic profile of brain tissues in exposed larvae and later as 6-month-old adults. High throughput RNA sequencing was conducted on brain tissues in unstressed and stressed conditions. Long-lasting effects of FLX were observed in telencephalon (Tel) and hypothalamus (Hyp) of adult zebrafish with 1927 and 5055 genes significantly (≥1.2 fold-change, false-discovery p-value < 0.05) dysregulated in unstressed condition, respectively. Similar findings were observed in Hyp with 1245 and 723 genes being significantly dysregulated in stressed adults, respectively. Differentially expressed genes converted to Homo sapiens orthologues were used for Ingenuity Pathway Analysis. The results showed alteration of pathways involved in neuroendocrine signaling, cholesterol metabolism and synaptogenesis. Enriched networks included lipid metabolism, molecular transport, and nervous system development. Analysis of putative upstream transcription regulators showed potential dysregulation of clocka and nr3c1 which control circadian rhythm, stress response, cholesterol metabolism and histone modifications. Several genes involved in epigenetic regulation were also affected by FLX, including dnmt3a, adarb1, adarb2, hdac4, hdac5, hdac8, and atf2. We report life-long disruptive effects of FLX on pathways associated with neuroendocrine signaling, stress response and the circadian rhythm, and all of which are implicated in the development of depressive disorders in humans. Our results raise concern for the persistent endocrine-disrupting potential of brief antidepressant exposure during embryonic development.